Single-cell and population level viral infection dynamics revealed by phageFISH, a method to visualize intracellular and free viruses - Allers, Elke; Moraru, Cristina; Duhaime, Melissa B.; Beneze, Erica; Solonenko, Natalie; Barrero-Canosa, Jimena; Amann, Rudolf; Sullivan, Matthew B. (Environmental microbiology, 2013)
Summary Microbes drive the biogeochemical cycles that fuel planet Earth, and their viruses (phages) alter microbial population structure, genome repertoire, and metabolic capacity. However, our ability to understand and quantify phage–host interactions is technique‐limited. Here, we introduce phageFISH – a markedly improved geneFISH protocol that increases gene detection efficiency from 40% to > 92% and is optimized for detection and visualization of intra‐ and extracellular phage DNA. The application of phageFISH to characterize infection dynamics in a marine podovirus–gammaproteobacterial host model system corroborated classical metrics (qPCR, plaque assay, FVIC, DAPI) and outperformed most of them to reveal new biology. PhageFISH detected both replicating and encapsidated (intracellular and extracellular) phage DNA, while simultaneously identifying and quantifying host cells during all stages of infection. Additionally, phageFISH allowed per‐cell relative measurements of phage DNA, enabling single‐cell documentation of infection status (e.g. early vs late stage infections). Further, it discriminated between two waves of infection, which no other measurement could due to population‐averaged signals. Together, these findings richly characterize the infection dynamics of a novel model phage–host system, and debut phageFISH as a much‐needed tool for studying phage–host interactions in the laboratory, with great promise for environmental surveys and lineage‐specific population ecology of free phages.